Sistem Dokumen Pelabuhan (SIDOLA) - Sahara, Siti; Fajar, Muhamad Nur; Arkan, Muhammad Thoriq (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research examines the implementation of SIMULASI SIDOLA (Port Document System) as an innovation in the one-door system at Sunda Kelapa Port. The main objective of this system is to improve efficiency in the processing of goods documents, which is a critical aspect of port operations. The method used was literature study and direct observation of the work process at the port. The results showed that SIDOLA SIMULATION significantly reduced the processing time of documents from days to just a few hours. The system also improved transparency and accountability through process digitization and data integration between stakeholders. The study recommends wider adoption of similar systems in other ports in Indonesia to support the efficiency and advancement of the national maritime industry.